KEPEMIMPINAN OTORITER SEBAGAI FUNGSI, BUKAN IDENTITAS: ANALISIS FUNGSIONAL TERHADAP PENGAMBILAN KEPUTUSAN YESUS DALAM BINGKAI FILOSOFIS PLATO - Yutang, Agus Rosalena (TEOLOGIS, RELEVAN, APLIKATIF, CENDIKIA, KONTEKSTUAL, 2026)
This study aims to deconstruct the negative meaning of the term "authoritarian" in contemporary leadership discourse by clearly distinguishing between authoritarianism as an identity inherent in the leader and authoritarianism as a function that can be legitimately exercised under certain conditions. Using library research method with a qualitative-philosophical approach, this study analyzes two main sources: Plato's thought on the Philosopher-King in the Allegory of the Cave (Republic Books V-VII) and the moments of Jesus' unilateral decision-making in the canonical Gospels. The results show that Plato offers a model of functional authoritarian leadership in which the Philosopher-King is obligated to lead firmly to liberate society from ignorance, based on knowledge of the highest truth and for the purpose of the common good. In the Gospels, four moments are identified where Jesus made unilateral decisions: the forgiveness of the woman caught in adultery, healing on the Sabbath, the calling of the first disciples, and the cleansing of the Temple. These actions were always based on claims of unique authority, aimed at the liberation of others, and undertaken with a willingness to pay a high price. Based on the synthesis of Plato's thought and Jesus' practice, four conditions for the legitimacy of authoritarian leadership are formulated: epistemological condition (possession of objective truth), teleological condition (purpose of liberation), situational condition (context requiring decisiveness), and moral condition (integrity and humility). These four conditions are cumulative and must be fulfilled simultaneously; otherwise, authoritarianism degenerates into tyranny. This study contributes to the development of a more nuanced leadership theory by distinguishing function from identity, and provides a critical framework for evaluating claims of authoritarian leadership.